Student Evaluation of Teaching: A Tool for the Assessment of Teaching Learning Practices in Higher Education Institutions - Joshi, Prem Raj; Pant, Prakash Raj; Chand, Rajendra Bir (KMC Journal, 2024)
Student Evaluation of Teaching (SET) is a way to evaluate the teaching effectiveness of teachers, and teaching-learning practices based on students' feedback. It is an evaluation of the teachers by students. SET is considered a tool to assess teaching effectiveness mostly in higher education institutions. Globally, universities use SET, especially in taking the decision of tenure and promotion of professors. This article attempts to gather students' responses regarding the teaching performance of their teachers from one of the campuses in Kailali district, Nepal. A survey research design was adopted to collect students’ responses. A random sampling method was employed to select undergraduate students from the selected campus. Students were asked to fill out a questionnaire consisting of the statements managed on a 5-point Likert scale. IBM SPSS Statistics 20 was used to manage and visualize the data, and the descriptive parameters were calculated for analysis. The results show that the teaching performance of the teachers was quite good in two categories, viz., management and motivation aspects, whereas the teaching performance in the instruction aspect was only satisfactory. This study shows that teachers need to improve their instructional strategies for the betterment of teaching and learning. The study will motivate other scholars and institutions to initiate the practice of SET for the enhancement of teaching and learning in their respective institutions.